Optimizing Dye-Sensitized Solar Cell Efficiency with a Triple Blend of Caesalpinia sappan L., Dracaena angustifolia, and Clitoria ternatea L. - Kusumawati, Nita; Rahmawati, Khofifatul; Setiarso, Pirim; Muslim, Supari; Zakiyah, Nafisatus; Fachrirakarsie, Fadlurachman Faizal (Universitas Jenderal Soedirman, 2025)
ABSTRACT. Dye-sensitized solar cells (DSSCs) offer a promising sustainable solution to global electricity challenges by converting sunlight into electricity using photosensitive dyes. This study explores the performance of DSSCs using natural dyes from sappanwood (Caesalpinia sappan L.), pandan leaves (Dracaena angustifolia), and telang flowers (Clitoria ternatea L.). Extraction of the dyes was done through maceration, with combinations made in single, double, and triple-component blends. UV-Vis spectroscopy showed increased light absorption in the 400-700 nm range. Combination F5 uniquely showed absorption peaks at 534.22, 573.64, 619.12, and 664.21 nm, which were affected by nine conjugated double bonds and electron transfer from C=C and carbonyl groups. Comparative band gap energy analysis showed that the triple-blending dyes exhibited the lowest energy range of 0.3392-0.4469 eV, compared to the double dye (0.4549-0.5778 eV) and single dye (0.4541-0.6248 eV), indicating better light harvesting ability. FTIR analysis confirmed the chemical structure of the dye. Prominent spectroscopic features include a broad band of 3332 cm-1 for hydroxyl groups, peaks at 2919 cm-1 and 1732 cm-1 representing alkane and carboxyl groups in cellulose, and an aromatic lignin C=C stretch at 1672 cm-1. The optimized F5 blend (1:2:1 ratio) achieved the highest solar cell efficiency of 3.24% with a band gap of 0.3392 eV. These results validate the potential of natural dye blends as DSSC sensitizers, showing enhanced absorption spectrum, improved stability, and increased electric current generation. Keywords: Dye-sensitized solar cells, Triple-component blending, Caesalpinia sappan L., Dracaena angustifolia, Clitoria ternatea L.